Diabetes-related distress and associated factors among adult diabetes mellitus patients attending public hospitals in Gedio zone, southern Ethiopia: Mediation analysis - Alem Bayable Mersha; Atirsaw Shimekaw; Edom Gebremedhin; Jerusalem Sewalem; Andualem Bayih; Abel Desalegn Demeke; Simret Gebre (PLoS ONE, 2025)
Background Individuals with diabetes might experience distress due to their treatment regimen, interactions with physicians, interpersonal relationships, and emotional well-being. This may lead to lower self-efficacy, which would impair self-treatment adherence and result in poor glycemic control. Understanding and addressing gaps may help individuals with diabetes improve their glycemic control. Therefore, this study aimed to determine the magnitude of diabetes-related distress and associated factors among adult diabetes mellitus patients attending public hospitals in the Gedio zone, Southern Ethiopia. Method An institutional-based cross-sectional study was conducted from April to May 2024 at four public hospitals in the Gedio zone. Study participants who met the inclusion criteria were selected using systematic random sampling techniques. Data were collected using the Diabetes Distress Scale (DDS-17). Both bivariable and multivariable ordinal logistic regression were applied. In multi-variable ordinal logistic regression, a P value < 0.05 significant level was used to identify factors of diabetic-related distress. Mediation analyses were conducted using the bootstrapping technique. A variable showing a significant indirect effect was considered as a mediator. Results In this study, a total of 506 adult patients with diabetes participated. The overall prevalence for moderate and high levels of diabetes-related distress was 47.04% (95% CI;42.6–51.5) and 41.5% (95% CI; 37.2–45.9), respectively. Variables like never had planned physical activity (adjusted odd ratio, aOR=3.09;95%CI = 1.034–9.28; P = 0.04), poor social support (aOR=3.44;95%CI = 1.42–8.33;P < 0.006), complications (aOR=1.79; 95%CI = 1.13–2.84; P < 0.013) and high blood pressure (aOR= 1.85; 95%CI = 1.12–3.05; P = 0.016) were factors for diabetes related distress. Depression was identified as a partial mediator of the relation between social support and diabetes related distress. Conclusion Diabetes-related distress was highly prevalent in diabetes patients. Healthcare providers need to address this by integrating psycho-social care with collaborative medical care.